The relationship between clinical and recovery dimensions of outcome in mental health - Macpherson, Rob; Pesola, Francesca; Leamy, Mary; Bird, Victoria; Le Boutillier, Clair; Williams, Julie; Slade, Mike (Elsevier, 2015)
Background: Little is known about the empirical relationship between clinical and personal recovery.